New techniques for robust beamformer design - Yu, Zhuliang (2008)
Some new techniques for robust beamformer design are presented in this thesis. Firstly, we extend the generalized sidelobe canceller to work with arbitrary channel impulse function. Then the power maximization method is used to develop robust beamformers which combat time delay error, generalized phase error and arbitrary array steering vector error. We also proposed a robust beamformer method for speech enhancement in the presence of strong stationary noise.